Financial Globalization : A Glass Half Empty? - Schmukler, Sergio L.; Abraham, Facundo (World Bank, Washington, DC, 2017)
Since the 1970s, the world has embarked on a new financial globalization era. Cross-country capital flows have significantly increased in developed and developing countries. However, the characteristics of financial globalization differ from what was originally expected. Various examples illustrate this point. Although the literature predicted large gains from financial globalization (such as additional funding, broad diversification, and deeper financial systems), the positive effects have been more limited. In developed and developing countries, financial globalization has manifested in increasing gross capital flows (inflows and outflows) rather than larger net flows. Capital markets are segmented and only a few large firms access international markets. International institutional investors do not seem to have played a stabilizing role, helping to exacerbate and transmit crises across countries. Although financial globalization has brought several beneficial changes, its net effects and spillovers to the overall economies participating in it have yet to be understood.